Trees in the religions of early medieval England - Bintley, Michael D. J. (Boydell Press, 2015)
Trees were of considerable importance in Anglo-Saxon religion, both Christian and pre-Christian. This book considers various ways in which trees featured in both, and how they helped to mediate the transition between the two. It argues that trees retained certain symbolic characteristics in Anglo-Saxon belief because of their importance to both heathens and Christians, notably the life-sustaining abundance of the earth. Archaeological, historical and textual evidence is used to present a comprehensive picture. Michael D.J. Bintley is Senior Lecturer in Medieval English Literature at Christ Church University, Canterbury
Title from publisher's bibliographic system (viewed on 11 Jun 2021)
Holy trees and inculturation in the conversion period -- Anglo-Saxon holy trees and their Northern European counterparts -- Rewriting the Holy Rood in Anglo-Saxon spiritual history -- The human forest: People and trees in Early Medieval England and Scandinavia
Keywords: Geschichte 400-1100; Trees / England / History / To 1500; Trees / England / Religious aspects; Baum; Religion; Great Britain / History / Anglo-Saxon period, 449-1066; England